2018
DOI: 10.3899/jrheum.170748
|View full text |Cite
|
Sign up to set email alerts
|

Occupation, Physical Workload Factors, and Disability Retirement as a Result of Hip Osteoarthritis in Finland, 2005–2013

Abstract: Our results suggest that education and physical workload factors appear to be the major reasons for excess disability retirement as a result of hip OA in manual occupations, particularly among men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(66 citation statements)
references
References 34 publications
1
64
0
1
Order By: Relevance
“…This is concerning as the rapid distributional change resulting from the process of urbanisation may exert limited impacts, if any, on reducing the inequalities. Previous studies found that farming in China is very labour intensive, which has a long-term detrimental effect on the physical functioning of those in their later life [ 40 , 41 ]. Such an effect can be accumulative without necessarily being apparent at an younger age despite serious health consequences on older persons [ 2 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is concerning as the rapid distributional change resulting from the process of urbanisation may exert limited impacts, if any, on reducing the inequalities. Previous studies found that farming in China is very labour intensive, which has a long-term detrimental effect on the physical functioning of those in their later life [ 40 , 41 ]. Such an effect can be accumulative without necessarily being apparent at an younger age despite serious health consequences on older persons [ 2 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology behind higher osteoarthritis rates in agricultural workers is unclear. Agriculture is a physicallydemanding occupation, and some studies have shown an association between high physical workload and osteoarthritis [11][12][13][14]. In a study of hip and knee arthroplasty by occupation, using sedentary occupations as a control group, male farmers had an odds ratio (OR) of 5.1 for knee replacement and 3.6 for hip replacement, higher than four other physically-demanding occupations [15].…”
Section: Introductionmentioning
confidence: 99%
“…For the analysis, the occupations were aggregated to two-digit level. The description of occupations at the two-digit level has been reported elsewhere (Solovieva et al 2018 ).…”
Section: Methodsmentioning
confidence: 99%